Optometrists’ perceptions of vision impairment services in public hospitals of Limpopo province - Modjadji M. Leshabane; Nishanee Rampersad; Khathutshelo P. Mashige (African Journal of Disability)
Background: Vision impairment (VI) services aim to mitigate the effect of VI and provide opportunities for visually impaired individuals to actively participate in their daily activities.